Complex degree of coherency inherent to laser images of blood plasma polycrystalline networks - Ushenko, Yu.A.; Istratiy, V.V.; Dubolazov, A.V.; Angelsky, A.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Given in this paper are theoretical basics for correlation-phase analysis of laser images inherent to human blood plasma. Also presented are comparative results of measurements aimed at coordinate distributions of the module of complex degree of coherency (CDC) and complex degree of mutual polarization (CDMP) of laser images describing blood plasma of a healthy person as well as of a patient with prostate cancer of the first stage. The authors investigated both values and ranges of changing the statistical (moments of the first to fourth orders), correlation (coefficients of the GrammCharlie expansion for autocorrelation functions) and fractal (slopes and dispersion of extremes for logarithmic dependences of power spectra) parameters for coordinate distributions CDC and CDMP. Determined are objective criteria for diagnostics of cancer changes in blood plasma of a patient with cancer.